Performance Assessment: How it Depends on Structural Economic Vulnerabilty and Human Capital. Implications for the Allocation of Aid - Patrick Guillaumont; Mark Mcgillivray; Laurent Wagner (Fondation pour les études et recherches sur le développement international (FERDI), 2013)
Developing country performance with respect to economic policies and institutional behaviour is a common criterion for the allocation of aid among recipient countries. This paper questions the manner in which performance is used in this regard, arguing that performance is too narrowly defined. A more appropriate definition is one that controls for the economic vulnerability and human capital of developing countries. Econometric analysis of cross-section and panel data is presented that supports this contention. The paper also contends that performance and exogenous economic shocks are likely to be pro-cyclical. This implied a double punishment when aid is allocated according to performance. Evidence of such punishment is also provided in this paper. The paper concludes by arguing that economic vulnerability and human capital variables should augment performance measures in aid allocation decision making.
Keywords: F35; O19; 330